Sequence of hydrographic changes in NW Mediterranean deep water due to the exceptional winter of 2005 - Jordi Font; Pere Puig; Jordi Salat; Albert Palanques; Mikhail Emelianov (Scientia Marina, 2007)
Time series measurements at a mooring site on the deep slope of the NW Mediterranean from October 2003 to July 2005 revealed the sequence of effects of the anomalously dry, markedly cold, and very windy winter of 2005 in deep water thermohaline properties. At the end of January, a dense water mass that was warmer and saltier than usual reached the deep slope mooring site. Almost simultaneously, the start of deep dense shelf water cascading episodes was observed in the Gulf of Lions’ submarine canyons. 30 days later, colder, fresher and even denser waters reached the mooring, with a 5-day delay from an intensification of the Gulf of Lions’ cascading. The signature of these waters was detected for 35 days, and by late spring 2005 a new stable water mass situation was reached, with higher thermohaline values than those that characterised the deep layer from October 2003 to January 2005.